Pengembangan Komoditas Batik: Determinasi Budaya Ekonomi dan Perubahan Struktur Kebijakan Terhadap Perkembangan Usaha Ekonomi Lokal (Studi Tentang Pengusaha Batik Laweyan Surakarta) - Erma Setiawati; Nursiam Nursiam; Zulfikar Zulfikar (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
Batik is an Indonesian national culture product that awarded by UNESCO as world cultural heritage. The research takes place in Kampung Batik Laweyan Surakarta which is the oldest and the center of the traditional batik industry in Indonesia. The purpose of this research is 1) to understand the characteristics of economic culture to look at the social culture of Laweyan Batik business, 2) to explain the development of batik trading which is supported by informal economic opportunities, 3) to analyze the changes in political (policy) structure and its anticipating setrategy. This research is a qualitative research using ethnographic approach. The results showed that 1) batik entrepreneurs in Laweyan characterized as bazaar economy culture with reciprocity social relationships, 2) the business relationship is based on trust, 3) government policy on financial assistance for the development of batik Laweyan plays an important role as anticipation to free trade.